Alignment of product design and supply chain for enhancing sustainability and coordination in industries - Forouzandeh, Mohammad (Privietlab, 2025)
Choosing a project portfolio to improve sustainability in the supply chain is a vital issue for industries. The main goal of the portfolio is to align the organization’s strategic objectives with project selection, ensuring that these projects make a meaningful contribution to the overall sustainability of the portfolio. This research specifically examines the integration of product portfolio design and supply chain design in the construction industry. The study utilizes an analytical model and optimization techniques to propose innovative solutions aimed at enhancing the alignment between suppliers and the product portfolio. Improving the efficiency and flexibility of the supply chain is accomplished through optimal coordination of both the product portfolio and the supply chain portfolio. This research explores how supply chain networks align with the product portfolio, focusing on creating flexibility in product portfolio management processes, managing changes, and addressing variability in different characteristics. The results indicate that effective and timely integration of product portfolio design with supply chain design can lead to reduced organizational costs and increased overall productivity. Improved coordination and integration between suppliers and final products have resulted in enhanced supply chain performance and lower ongoing organizational expenses.